BIOPESTICIDE MADE FROM RICE STRAW - Moh. Hoesain; Wiwiek Sri Wahyuni (UNEJ e-Proceeding, 2017)
Rice straw is found abundantly in rice fields because the average straw produced from rice field area is 1.4 times the amount of its harvest. If the straw is composted, the yield ofcompost is 60%. This compost was made as a biopestisida after added with bacteriumPseudomonas putida H10. Beside of this, it also acted as biofertilizer because it was rich innutrient content. When rice crops were sprayed three times with this biopesticide, the plantswere resistance to rice blast and neck rot disease (Piricularia oryzae) and brownplanthopper that attacked the area at that time, and increased the growth. This was indicatedby the more number of tillers, more greener leaves, panicles were grown earlier, so that wereharvested five days earlier than that plants not sprayed wih biopesticide. This biopestisidewas also tested on tomato plants in order to control Fusarium wilt disease. It was sprayed inthe earlier growth, the flowering and fruiting periods. It was turn out that this tomatoes wereresistance to Fusarium wilt, thrips and leaf-eating pheasants (Spodoptera litura), alsogrowing much better and more dense fruits.